2008
DOI: 10.1080/02844310801924373
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the learning curve for the treatment of morphoeic (sclerosing) basal cell carcinoma of the face

Abstract: The treatment of morphoeic (or sclerosing) basal cell carcinoma (mBCC) of the face is associated with high rates of incomplete excision and recurrence. A principal risk factor for incomplete resection is the grade of surgeon. We did a prospective, randomised study of 40 consecutive patients with mBCC of the face. The extent of the tumour was assessed under standard conditions by consultant surgeons and compared with assessments by resident surgeons with the help of the Varioscope, a combination of microscope a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…3,8,21,26,27 In contrast, Kumar et al 9 concluded that the incidence of incomplete excision is not related to the experience of the surgeon. 3,8,21,26,27 In contrast, Kumar et al 9 concluded that the incidence of incomplete excision is not related to the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8,21,26,27 In contrast, Kumar et al 9 concluded that the incidence of incomplete excision is not related to the experience of the surgeon. 3,8,21,26,27 In contrast, Kumar et al 9 concluded that the incidence of incomplete excision is not related to the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to significant cosmetic disfigurement, especially when the face is involved. 5,8 Incomplete excision remains a frustrating problem because it leads to a significant reoperation rate or prolonged follow-up, with concomitant patient discomfort and economic impact. 1,3Y5 A wide range of different treatments has been described for the management of BCCs, but conventional surgical excision is the treatment of choice for primary BCCs and is appropriate for most of the these tumors.…”
mentioning
confidence: 99%
“…17 Mixed histologic, micronodular, and morpheic subtypes are more likely to have margins involved by subclinical extension. 21 Baba and colleagues reported that Tzanck smear testing had high accuracy for margin control for well-demarcated BCC. 19 Shalom and colleagues recommend using a clinical stretch test before excision to help identify margins.…”
Section: Ncomplete Excision Of Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%
“…20 Erba and colleagues recommend high magnification and good lighting to enhance the ability of plastic surgeons to recognize morpheic BCC margins. 21 Baba and colleagues reported that Tzanck smear testing had high accuracy for margin control for well-demarcated BCC. 22 A meta-analysis *St John's Institute of Dermatology, St Thomas' Hospital, London, UK; † Toowoomba Eye and Skin Clinic, Toowoomba, Queensland, Australia by Rogalski and colleagues reported that incomplete excision was 2.5 times as likely on the ear or nose.…”
Section: Ncomplete Excision Of Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%